2014
DOI: 10.1007/s10464-014-9693-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Community Resilience Factors Among Lesbian, Gay, Bisexual, Queer and Questioning Youth and Adults in Israel

Abstract: Drawing on resilience theories, this study examined the individual and community factors of Israeli lesbians, gays, bisexuals, queers, and questioning (LGBQs) that contribute to positive mental health and the degree to which individual and community protective factors mitigate the adverse effect of risk factors for poor mental health. Differences in resilience factors between LGBQ youth and adults were explored. Data were collected on 890 LGBQ youth and adults. Findings emphasize the role of community-level re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 43 publications
2
50
1
1
Order By: Relevance
“…In spite of experiences of marginalization and discrimination, many GBM do not go on to develop mental health conditions or engage in harmful substance use. Shilo, Antebi, and Mor (2015) found that factors such as support of family and friends, meaningful connections with the LGBT community, and having a steady partner, protect against developing poorer mental health in lesbian, gay, bisexual, queer, and questioning adults. Thus, more focus on factors such as these that promote resiliency in GBM would be beneficial to include in future research on mental health and substance use in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of experiences of marginalization and discrimination, many GBM do not go on to develop mental health conditions or engage in harmful substance use. Shilo, Antebi, and Mor (2015) found that factors such as support of family and friends, meaningful connections with the LGBT community, and having a steady partner, protect against developing poorer mental health in lesbian, gay, bisexual, queer, and questioning adults. Thus, more focus on factors such as these that promote resiliency in GBM would be beneficial to include in future research on mental health and substance use in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, both groups are not visible minorities (in contrast to racial minorities and people with physical disabilities) and may not be recognizable at first contact. Third, according to the literature, both groups are stigmatized minorities (Harré, ; Hoyt, Morgenroth, & Burnette, ; Moss‐Racusin & Rabasco, ; Van Roekel et al, ; Shilo, Antebi, & Mor, ) and are sometimes socially excluded. That is, they may lack social contact and friendship networks.…”
Section: Research Settingsmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t that social support is important in maintaining positive psychological health in the face of adversity (e.g., House, Umberson, & Landis, 1988;Southwick et al, 2005;Thoits, 1995;Wilson & Gillies, 2005) and in particular, studies have demonstrated the importance of supportive others, both LGBTI and heterosexual alike, in fostering resilience among LGBTI people (Gray et al, 2015;Scourfield et al, 2008;Shilo et al, 2015). Within this study, social support not only provided emotional and instrumental support, but it also challenged internalized negative beliefs of being non-heterosexual, provided acceptance, and fostered a sense of belonging.…”
Section: And Sense Of Belonging (Mccallummentioning
confidence: 99%
“…LGBTI resilience-focused studies have uncovered additional protective factors which include safe and supportive others, safe places, resisting discrimination, viewing sexuality as natural, optimism and hope, emotional processing, being out, and being in a relationship (Foster, A c c e p t e d M a n u s c r i p t & McDermott, 2008;Shilo, Antebi, & Mor, 2015). These protective factors have yet to be examined within the context of family rejection so it is unknown if and how they may buffer such adversity.…”
mentioning
confidence: 99%